Bagaimana Mahasiswa Bisa Menulis Artikel Ilmiah? Studi Pengalaman FUAD UIN Mahmud Yunus Batusangkar - Susanti Vera; Hidayatul Fikra; Fitriani Fitriani; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to discuss the effectiveness of scientific article writing exercises among students. This research uses a qualitative approach with descriptive methods. The formal object of this research is training and mentoring. The material object is writing scientific articles. The scope of this research is undergraduate students. Meanwhile, the context is the Faculty of Ushuluddin Adab and Da'wah, Mahmud Yunus Batusangkar State Islamic University. The results of the research and discussion showed that 20 article manuscripts were achieved from a total of 45 student participants, where this success was supported by policy, student motivation, availability of modules, implementation of reviews and feedback, and excitement. This research concluded that training and mentoring were effective at the pre-, implementation and post-activity stages.